Degradation and stabilization of polyurethane elastomers. (March 2019) - Xie, Fengwei; Zhang, Tianlong; Bryant, Peter; Kurusingal, Valsala; Colwell, John M.; Laycock, Bronwyn
Graphical abstract: Abstract: Polyurethane elastomers have a combination of excellent mechanical, physical and chemical properties along with exceptional biocompatibility. Therefore, these elastomeric systems are used in a diverse range of indoor, outdoor, underwater and biomedical applications. However, under certain conditions polyurethane elastomers undergo degradation, resulting in modified properties during usage or even complete failure. The degradation will not only severely affect the quality of the associated items, devices, or instruments, but may also cause catastrophic outcomes risking people's safety and health. This review presents a comprehensive survey of the literature regarding various types of degradation of polyurethane elastomers, including photo-, thermal, ozonolytic, hydrolytic, chemical, enzymatic, in-vivo / in-vitro oxidative, biological, and mechanical degradation. The stability of polyurethane elastomers based on different building blocks of macrodiols (polyester, polyether, polycarbonate, polybutadiene, and polyisobutylene), isocyanates (aromatic and aliphatic), and chain extenders (diols, triols, and diamines) are summarised, and the mechanisms of different types of degradation are presented. The chemical components significantly influence not only the material structure and properties but also the degradative stability. Focussing on the components, we explore strategies for the enhancement of polyurethane stability through chemistry and engineering. A range of stabilizers, including both organic and inorganic additives for better stability against different types of degradation, are discussed, with a focus on their efficacy and mechanisms of action. A perspective on novel polyurethane materials with desired structures and properties combined with exceptional stability is also provided.